2004
DOI: 10.1111/j.1523-1755.2004.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of renal LAT1 and LAT2 and enhanced L-DOPA uptake in SHR immortalized renal proximal tubular cells

Abstract: Differences in L-DOPA handling between SHR and WKY cells may result from over-expression of LAT1 and LAT2 transporters in the former. The unique role of Na(+)-dependent transporters (system B(0)) in SHR cells also contributes to the enhanced L-DOPA uptake in these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…Recently, we reported that overexpression of type 2 Na ϩ -independent L-type amino acid transporter (LAT2) in the SHR kidney may contribute to the enhanced L-DOPA uptake (41). In line with these findings, immortalized renal proximal tubular epithelial cells from the SHR also overexpressed LAT2 (42). However, only 25% of L-DOPA uptake in SHR cells occurred through LAT2; 50% of L-DOPA occurred through LAT1 and the remaining 25% through Na ϩ -dependent transport systems.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Recently, we reported that overexpression of type 2 Na ϩ -independent L-type amino acid transporter (LAT2) in the SHR kidney may contribute to the enhanced L-DOPA uptake (41). In line with these findings, immortalized renal proximal tubular epithelial cells from the SHR also overexpressed LAT2 (42). However, only 25% of L-DOPA uptake in SHR cells occurred through LAT2; 50% of L-DOPA occurred through LAT1 and the remaining 25% through Na ϩ -dependent transport systems.…”
supporting
confidence: 71%
“…Discrepancies between the present study and the findings previously reported (42), namely on the expression of LAT2 in 12-wk-old SHR relative to WKY observed in the latter, may be related to the use of different experimental methods (Northern blot vs. quantitative RT-PCR) to detect LAT2 mRNA. However, it should be underlined that the results on differences in the abundance of LAT2 transcript in 4-wk-old SHR and WKY reported here using quantitative RT-PCR and those in a previous study (42) using Northern blot techniques were identical.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…3). The inhibitory effect of dopamine on Na ϩ -K ϩ -ATPase is influenced by intracellular sodium and calcium; dopamine inhibits Na (86,164,165). L-DOPA is the sole source of renal tubular dopamine production.…”
Section: Renal Dopamine Receptorsmentioning
confidence: 99%